Conceptual Art, Theology, and Re-Presentation - Jonathan A. Anderson (Religions, 2022)
Within the vast and varied scholarship of contemporary art, the relations between conceptual art and religion generally have not received careful investigation. There are, however, potentially quite subtle and complicated interrelations in play here that warrant closer study. This article develops and expands such study, first, by clarifying how procedural and re-presentational ways of thinking function in conceptual art, and, second, by showing how these help us to identify six general “logics” within which the interrelations of conceptual art and religion might be reexamined in the histories of contemporary art, both critically and constructively. These six categories are helpful heuristic guides, but each must be substantiated through fine-grained investigations of particular artists and artworks, and each involves “religion” in ways that open into and require particular theological modes of questioning. Therefore, third, this article then turns to a case study of contemporary Belgian artist Kris Martin, focusing especially on For Whom (2012), a work featuring a readymade two-ton church bell that swings on the hour but without a clapper (and thus without sound). Martin’s work consistently re-presents Christian forms and artifacts in compromised states—vacant altarpieces, broken statuary, etc.—invoking histories of European secularization while also retrieving and reactivating theological questions and grammars within those histories. By clarifying these various points of reference, particularly in dialogue with John Donne (from whom Martin borrows his title), this study attends to one instance of a significant interfacing of conceptual art, religion, and theology.